KONTRIBUSI KEPEMIMPINAN TRANSFORMASIONAL KEPALA TK DAN PENGARUH KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH DAN IKLIM SEKOLAH TERHADAP EFEKTIVITAS SEKOLAH - Gustria Sari (Universitas Pendidikan Indonesia, 2013)
Pengelolaan efektivitas sekolah merupakan hal urgen terutama di SDN. Penelitian ini tujuannya mengetahui gambaran kepemimpinan instruksional kepala sekolah, iklim sekolah dan efektivitas sekolah serta menganalisis pengaruh secara parsial maupun simultan terhadap efektivitas sekolah di SDN. Metode penelitian yang digunakan menggunakan pendekatan kuantitatif, dengan metode survey dan angket sebagai instrumennya, populasi 30 SDN, sampel 95 guru di SDN Kecamatan Katapang. Hasil penelitian menunjukan bahwa gambaran kepemimpinan instruksional kepala sekolah, iklim sekolah, dan efektivitas sekolah pada kategori sangat tinggi, Kepemimpinan instruksional kepala sekolah dan iklim sekolah berpengaruh dan signifikan terhadap efektivitas sekolah. Temuan penelitian, peran kepala sekolah sebagai pemrakarsa inovatif dan kreatif perubahan/kemajuan pendidikan, minat profesional guru, dukungan orang tua, motivasi siswa, dan prestasi siswa masih rendah. Rekomendasi, meningkatkan kompetensi dan ketrampilan kepala sekolah, memfungsikan wadah MKKS, tumbuhkan komitmen dan dedikasi tinggi sebagai guru profesional bagi guru, orang tua menjadi mitra sekolah , dan pelaksanaan program Diklat dan PKB bagi kepala sekolah dan guru oleh Dinas Pendidikan Kecamatan, Kabupaten, dan Propinsi. This is what underlies the important of school effectiveness especially in elementary public school. This research purpose is to find out the description of school effectiveness with the factors which influence it such as the Head master instructional leadership and school climate. And also analyze the major influence of those two factors toward school effectiveness in the Katapang Subdistrict Elementary Public School. The methodology used is quantitative approach,survey, The population number is 30 elementary school and the sample number is 95 teachers. The conclusion of this research is the general description about headmaster instructional leadership, school climate and school effectiveness is also in very high category. Head master instructional leadership and school climate give positive and quite significant influence toward school effectiveness. In this research is also found indicator of they are the role of head master as the person who is innovative and creative in developing and enhancing education, teacher professionalism interest, parent’s support, student motivation and student’s achievement is low level. Based on the findings, writer recommends the headmasters to improve the competence and skill as headmaster and the function MKKS organization for teacher to increase high commitment and dedication as a professional teacher, for parents to be a great school partner, and to the education institutions which are responsible in subdistrict/city/district to arrange training for headmaster and PKB program for teacher .